High performance work systems and employee mental health: The roles of psychological empowerment, work role overload, and organizational identification - Kim, Kyoung Yong; Messersmith, Jake G.; Pieper, Jenna R.; Baik, Kibok; Fu, Sherry (Qiang) (Human Resource Management, 2023)
AbstractEmployee mental health is a central issue in today's global workplace. This paper analyzes the effect of high performance work systems (HPWSs) on employee mental health. We integrate HPWS concepts with job demands‐resources (JD‐R) theory to examine competing theoretical perspectives—a positive HPWS influence and a negative HPWS influence on employee mental health. We examine employees' perceptions of psychological empowerment as an indicator of the motivational pathway of the JD‐R and work‐role overload as an indicator of the strain pathway to explain the differential effect of HPWSs on mental health. We also incorporate organizational identification theory to demonstrate how one's identification with the organization can either accentuate or attenuate feelings of both psychological empowerment and work‐role overload. Findings from a study of 999 employees in 174 South Korean organizations indicate that HPWSs are positively associated with employee mental health via employee perceptions of empowerment and that HPWSs are negatively associated with employee mental health through perceptions of work‐role overload. Furthermore, the study finds that organizational identification attenuates the relationship between HPWS and both empowerment and overload. Practice‐level post hoc analyses also reveal that the job design characteristics, pay level, and participative decision‐making are linked to empowerment. In addition, participative decision‐making is most strongly associated with work overload.